Public Finance and Social Protection System Reforms in Mexico: Part II. (1st May 2013) - Chávez Presa, Jorge A.; Trillo, Fausto Hernández; López‐Calva, Luis Felipe; ,
Abstract : Mexico needs a proposal to integrate reforms into the social protection system as an indispensable factor for social cohesion with holistic fiscal reforms that create and nurture viability in the long term and improve the country's competitiveness. There is also a need for reforms that seek to break through the prevailing economic stagnation and provide the nation with medium‐ and long‐term development opportunities. Specifically, it needs a proposal that addresses the overwhelming need to formalize a new social contract based on justice and sustained by economic growth that allows Mexico's democracy to work for all of its residents. This document seeks to conduct an exercise that is rarely attempted in Mexico: establish achievable short‐ and medium‐term goals for universal social protection tied to revenue sources that provide long‐term viability and sustainability.